Pengaruh Gaya Kepemimpinan Transformasional dan Disiplin Kerja terhadap Kinerja Karyawan Melalui Motivasi Di PT. Bank Negara Indonesia (PERSERO) Tbk Cabang Jambi - Sanezara, Garien Eksta; MS, M. Zahari; Yamali, Fakhrul Rozi (Universitas Batanghari, 2024)
This research aims to determine the description of transformational leadership style, work discipline, motivation and employee performance, analyzing and testing the influence of transformational leadership style and work discipline on employee performance through employee motivation as a mediating variabel. This research uses the PLS analysis method. Based on the research results, transformational leadership style and work discipline have a positive and significant effect on work motivation. Transformational leadership style, work discipline and motivation have a positive and significant effect on employee performance. The transformational leadership style has a positive and significant effect on employee performance through motivation, while work discipline does not have a significant effect on employee performance through work motivation at PT. Bank Negara Indonesia (Persero) Tbk Jambi Branch.Â